Perbaikan Blow-By Gas Engine Bulldozer Cat D3k-2xl - Ramli, Ismail; Cipta, Denny Hendra; Munir, Hamka; Amin, Al; Walijan, Walijan (Syntax Corporation, 2025)
Blow-by is a condition in which combustion gases from the combustion chamber escape through the piston and piston ring gap into the crankcase. This symptom leads to reduced engine performance, increased fuel consumption, and accelerated component wear. This research aims to analyze the causes of blow-by in the Caterpillar D3K-XL Bulldozer engine and to determine the appropriate troubleshooting steps. The research methods include field study, operator interviews, and direct inspection of engine components such as piston rings, cylinder liners, and valves. The results indicate that the main causes of blow-by are worn piston rings and scratches on the liner wall due to insufficient periodic maintenance. Corrective actions were carried out through replacement of worn components, cleaning, and reassembly according to manufacturer standards. These improvements successfully restored engine performance and minimized the risk of further damage.